Development of Nanoradiopharmaceuticals by Labeling Polymer Nanoparticles with Tc-99m - Patricio, B. F. de Carvalho; Albernaz, M. de Souza; Santos-Oliveira, R. (World Journal of Nuclear Medicine, 2013)
Nanomedicine is considered as the future of modern medicine. Hence, serious global efforts are being made for the development of nanopharmaceuticals. Among all the nanopharmaceuticals developed so far, radiopharmaceuticals constitute only a very small portion, as noted in the published literature. The procedures for development of nanoradiopharmaceuticals are complex. In this paper we discuss the results of a research directed at developing nanoradiopharmaceuticals based on three different types of nanopharmaceuticals as alternative drug delivery systems.
Keywords: Drug delivery system; nanobiotechnology; nanomedicine; radiopharmaceuticals